Lack of genetic population structure of slimy sculpin in a large, fragmented lake. Issue 3 (24th November 2017) - Euclide, Peter T.; Flores, Natalie M.; Wargo, Matthew J.; Kilpatrick, C. William; Marsden, J. Ellen
Abstract: Most of what is known about sculpin population structure comes from research in streams; however, slimy sculpins are also a common benthic species in deep lakes. In streams, sculpins are considered to be a relatively inactive species, moving only small distances, and characteristically have high levels of genetic structure. We examined population genetic structure of slimy sculpin ( Cottus cognatus ) across multiple barriers and over distances up to 227 km in Lake Champlain (USA, Canada) and Lake Ontario (USA, Canada) to determine whether lake populations of sculpin are also highly structured. We predicted that slimy sculpin populations in Lake Champlain would be structured by six causeways as well as by distance, Lake Ontario populations would be structured only by distance, and differences between the lakes would be large relative to within‐lake differences. We examined microsatellite variation among 200 slimy sculpins from Lake Champlain and 48 slimy sculpins from Lake Ontario to evaluate patterns of population connectivity and structure. There was no indication of population substructuring within either lake but sculpin were genetically distinct between lakes. We conclude that there is a single, panmictic population of sculpin present in Lake Champlain and another potentially panmictic population in Lake Ontario, with no indication of genetic isolation by distance. Our results contrast with data from sculpin in streams, suggesting distance and habitat fragmentation exert little influence on population connectivity of benthic fish in lakes.